Ameliorating Effect of Hypothalamic Brain-Derived Neurotrophic Factor Against Impaired Glucose Metabolism After Cerebral Ischemic Stress in Mice - Shinichi Harada; Wakako Fujita-Hamabe; Shogo Tokuyama (Elsevier, 2012)
Brain-derived neurotrophic factor (BDNF), a member of the neurotrophin family, has potent neuroprotective effects against brain injury. We recently reported that glucose intolerance/hyperglycemia could be induced by ischemic stress (i.e., post-ischemic glucose intolerance) following ischemic neuronal damage. Therefore, the aim of this study was to determine the effects of BDNF on the development of post-ischemic glucose intolerance and ischemic neuronal damage. Male ddY mice were subjected to middle cerebral artery occlusion (MCAO) for 2 h. On day 1, the expression levels of BDNF were significantly decreased in the cortex, hypothalamus, liver, skeletal muscle, and pancreas. The expression levels of tyrosine kinase B receptor, a BDNF receptor, decreased in the hypothalamus and liver and increased in the skeletal muscle and pancreas, but remained unchanged in the cortex. Intrahypothalamic administration of BDNF (50 ng/mouse) suppressed the development of post-ischemic glucose intolerance on day 1 and neuronal damage on day 3 after MCAO. In the liver and skeletal muscle, the expression levels of insulin receptors decreased, while gluconeogenic enzyme levels increased on day 1 after MCAO. These changes completely recovered to normal levels in the presence of BDNF. These results indicate that regulation of post-ischemic glucose intolerance by BDNF may suppress ischemic neuronal damage. Keywords:: cerebral ischemic stress, brain-derived neurotrophic factor, insulin receptor, gluconeogenesis, middle cerebral artery occlusion